Study of Characterization and Concentration of Trace Element in Human Hair of Radiation Workers - Zahraa Abbas Rasheed (Journal of Global Pharma Technology, 2019)
Human hairs experience damage and restoration processes consistently because of various external and internal factors. To analyze degrees of hair damage, morphological studies based on scanning electron microscopy (SEM).The present study aims to analyze degrees of hair damage, morphological and structural changes in human hair shaft and effect concentration of trace element under SEM and ICP-OES respectively in a sample of male radiation workers who worked in Al-Tuwaitha nuclear site.  The descriptive statistics of grade of hair damage, hair diameter, cell length under SEM. A statistically significant difference was found between the radiation worker and control group with respect to the SEM scores with the extent of damage being more in the radiation workers as compared to the control groups. The present study showed high percentage of grading damage under SEM for both Radiation worker& control group in grade 1(56%) and grade 0(60%), respectively. To validate the analytical of levels of Sr and U in scalp hair of radiation workers and control groups. U levels in of radiation workers was  significantly higher in radiation workers compared to control groups, whereas, Sr was significantly lower in radiation workers as compared to the control group. In conclusion, the obtained results occupationally exposed to low levels of ionizing radiation may be associated with increased deposits on the hair shaft surface; these findings may be consistent with those obtained in other studies, confirming that the deficiency and efficiency of trace elements play a role in clinical disorders and the pathogenesis of many diseases. Furthermore, to prove that human hairs are useful in the studies pertaining to chronic body exposure and good biomarkers in clinical studies for radiation worker.Keywords: Human hair, SEM, ICP: OES, Uranium, Strontium.